(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
This study was conducted in Banda Aceh district by utilizing seismic refraction P- and S-waves methods on three similar profile lines, with the aim to identify subsurface characteristic. The seismic data were acquired using ABEM TERRALOC MK8 system with 28 Hz vertical and 6 Hz horizontal geophones, and suitable seismic sources. Software used for processing to produce 2-D tomography sections and interpretations are IXRefract, Microsoft Excel, SeisOpt@2D v6.0 and Surfer 8. The results show the study area comprises of four subsurface layers with strong to very strong relation between Vp and Vs (R2 is >0.7509) for each layer. Ratio value of Vp and Vs (Vp/Vs) for each layer (1st to 4th) was calculated to be 4.75 – 5.79; 6.50 – 8.89; 6.57 – 12.17 and 6.08 – 8.21 respectively. This study concluded that the ground subsurface in Banda Aceh district is made up of water saturated unconsolidated sediments that was identified to be a mixture of clay and silt at depth up to 55 m.